A new type of powder metallurgy material and its preparation method and application

By using raw materials such as water atomized iron powder, electrolytic copper powder and scale graphite with specific particle size distribution, powder metallurgy materials with high tensile strength and riveting performance are prepared, and the ductility and production of gas spring parts in the prior art are solved. The problem of high cost achieves efficient and low-cost preparation of gas spring fixing rings.

CN116265157BActive Publication Date: 2024-12-17YANGZHOU TIANJIAN MACHINERY MFR
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310110865.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-14
Publication Date
2024-12-17
Estimated Expiration
2043-02-14

AI Technical Summary

Technical Problem

Existing powder metallurgical materials are difficult to meet the high ductility requirements of gas spring parts, and at the same time they are high in production costs and low in efficiency. The use of zinc-aluminum alloy materials increases the production cost of gas springs.

Method used

Using water atomized iron powder, electrolytic copper powder and scale graphite with specific particle size distribution, powder metallurgy materials with high tensile strength and riveting performance are prepared through reasonable mixing ratios and process flow to replace zinc Aluminum alloy parts are prepared with gas spring fixing rings.

Benefits of technology

The high tensile strength and ductility of the gas spring fixing ring is achieved, which reduces production costs and improves production efficiency. The specific particle size distribution of the material and the selection of additives avoid the increase in the hardness of metallurgical materials and the influence of surface compounds, and improves density. Uniformity and ductility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of powder metallurgy technology, in particular to the field of IPC B22F1, and further to a new type of powder metallurgy material, a preparation method and application thereof. In terms of mass percentage, the material comprises the following raw materials: 0.1-0.5% non-metallic powder, 0.2-0.8% lubricant, 0.1-0.5% processing aid, and metal powder remainder. The new type of powder metallurgy material provided by the present invention is formed by die pressing, and then sintered at 1110°C in a mesh belt furnace to obtain a semi-finished product. The gas spring parts obtained by mechanical processing have good tensile strength and riveting performance, and are used to replace zinc-aluminum alloy parts to prepare gas spring fixing rings. The tensile strength is not only better than that of zinc-aluminum alloy, but also can meet the riveting performance required by the gas spring fixing ring. The production cost of the gas spring fixing ring can be reduced without affecting the use of the gas spring fixing ring, and the production efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of powder metallurgy, in particular to the field of IPC B22F1, and further to a novel powder metallurgy material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the automobile industry, consumers have higher and higher requirements for basic automobile parts, and the demand is also increasing. Gas springs are mainly used in the rear doors and engine hood systems of automobiles.

[0003] The system assists customers to open the back door and the engine hood, so the gas spring material should have high bending strength and elastic limit, good plasticity and toughness; the gas spring material on the market is mainly zinc-aluminum alloy, but the use of zinc-aluminum alloy material inevitably increases the production cost of gas springs. Powder metallurgy is an emerging material preparation technology with the characteristics of green, high efficiency, low carbon and sustainability. At present, developed countries abroad have carried out the research and development and production of powder metallurgy aluminum alloy parts, but because the general powder metallurgy material formula can ensure the strength of gas spring parts, but cannot meet their ductility requirements, the production of gas spring parts with powder metallurgy materials is limited.

[0004] Chinese patent CN104561773 B discloses a powder metallurgy material for a mold and a preparation method thereof. The materials are Zn, V, Ni, Sc, Si, Al, Nd, Ho, and the balance is Fe. The powder metallurgy material prepared by this technical solution has high tensile strength and anti-tensile strength, but the technical solution uses more raw materials, has high cost and long mixing time, and has low production efficiency. Summary of the invention

[0005] The first aspect of the present invention provides a novel powder metallurgy material, which comprises the following raw materials, by mass percentage: 0.1-0.5% non-metallic powder, 0.2-0.8% lubricant, 0.1-0.5% processing aid, and metal powder remainder.

[0006] In some preferred embodiments, the metal powder is selected from one or more combinations of iron powder, copper powder, aluminum powder, nickel powder, and chromium powder.

[0007] Preferably, the metal powder is selected from a combination of iron powder and copper powder.

[0008] Preferably, the iron powder is selected from one or more combinations of atomized iron powder, reduced iron powder, iron-nickel alloy powder, and iron-chromium alloy powder.

[0009] Preferably, the iron powder is atomized iron powder.

[0010] Preferably, the atomized iron powder is water-atomized iron powder.

[0011] Preferably, the particle size distribution of the water atomized iron powder is: particles with a particle size greater than 180 μm ≤ 1wt%, particles with a particle size less than 180 μm and greater than 150 μm ≤ 10wt%; particles with a particle size less than 45 μm are 15-30wt%, and the remainder of particles with a particle size less than 150 μm and greater than 45 μm.

[0012] Preferably, the water-atomized iron powder has a Mn mass content of ≤0.15%, a P mass content of ≤0.015%, and an S mass content of ≤0.015%.

[0013] In some preferred embodiments, the copper powder is selected from one or more combinations of atomized copper powder, electrolytic copper powder, bronze powder, and brass powder.

[0014] Preferably, the mass percentage of the copper powder is 0.5-2%.

[0015] Preferably, the mass percentage of the copper powder is 1%.

[0016] Preferably, the copper powder is electrolytic copper powder.

[0017] Preferably, the copper mass content of the electrolytic copper powder is ≥99.8%.

[0018] Preferably, the particle size distribution of the electrolytic copper powder is as follows: the maximum particle size is not greater than 100 μm, the particles with a particle size less than 100 μm and greater than 75 μm are ≤ 3 wt %; the particles with a particle size less than 75 and greater than 45 μm are 37-52 wt %, and the particles less than 45 μm are 45-60 wt %.

[0019] In some preferred embodiments, the non-metallic powder is selected from one or more combinations of carbon powder, silicon carbide powder, and silicon nitride powder.

[0020] Preferably, the non-metallic powder is carbon powder.

[0021] Preferably, the mass percentage of the carbon powder is 0.3%.

[0022] Preferably, the particle size of the carbon powder is 5-20 μm.

[0023] Preferably, the carbon powder is flake graphite.

[0024] Preferably, the carbon content of the flake graphite is ≥98.0%.

[0025] In the present invention, water-atomized iron powder with a specific particle size distribution, a Mn mass content of ≤0.15%, a P mass content of ≤0.015%, and an S mass content of ≤0.015% is used as a matrix material. By adding copper powder and carbon powder, especially when 1% of electrolytic copper powder and 0.3% of flake graphite are added, the prepared gas spring parts, especially the gas spring fixing ring, not only have good tensile strength, but also have good riveting performance, and can be used to replace zinc-aluminum alloy parts to prepare gas spring fixing rings. The applicant speculates that: the water-atomized iron powder particles are oval, the microstructure is fine, and the powder particle structure is dense. Compared with ordinary reduced iron powder, the water-atomized iron powder has good compressibility, high loose density, and fast flow rate, thereby improving the density uniformity of the gas spring fixing ring, and improving its tensile strength and riveting performance; by controlling the particle size of the water-atomized iron powder and the mass content of Mn, P and S in the water-atomized iron powder, it is possible to avoid the metallurgical material from increasing the hardness of the powder and forming surface compounds during the pressing process to affect the performance of the gas spring fixing ring; since the size of the electrolytic copper powder is smaller than that of the water-atomized iron powder, it can be evenly dispersed in the gaps of the water-atomized iron powder; in addition, since the electrolytic copper powder has a dendritic structure, a large specific surface area, and good surface activity, it can promote the connection of the water-atomized iron powder interface, which is beneficial to the mass transfer and diffusion of the powder interface. The electrolytic copper powder can react with the water-atomized iron powder during sintering to form an electrolytic copper powder phase interface between the water-atomized iron powder interfaces, which plays a reinforcing role. Flake graphite can not only reduce the friction of powder metallurgy materials during the pressing process, but also, due to its flaky shape, can be effectively embedded in the matrix material, thereby reducing the energy threshold required for the metal to transition from local plastic deformation to uniform plastic deformation, thereby improving its ductility; but if too much is added, due to the small density and light specific gravity of flake graphite, most of it exists in the matrix in a free state, which will increase the porosity of the matrix, resulting in a reduction in the cross-sectional area of ​​the gas spring retaining ring under stress during the stretching process, thereby reducing the tensile strength of the gas spring retaining ring.

[0026] In some preferred embodiments, the lubricant is selected from one or more combinations of zinc stearate, calcium stearate, magnesium stearate, and aluminum stearate.

[0027] Preferably, the lubricant is zinc stearate.

[0028] In some preferred embodiments, the processing aid is manganese sulfide or boron nitride.

[0029] Preferably, the processing aid is manganese sulfide.

[0030] In the present invention, by adding specific lubricants and processing aids, the raw materials in the powder metallurgy material can be prevented from component segregation, and the friction of the powder metallurgy material during the pressing process can be reduced. After the powder metallurgy material is sintered, manganese sulfide can be distributed near the sintering neck or in the pores to compensate for the additional impact of the pores.

[0031] A second aspect of the present invention provides a method for preparing a novel powder metallurgy material, comprising the following steps:

[0032] (1) Add 1 / 3~1 / 4 of iron powder, copper powder, non-metallic powder, lubricant and processing aid into a mixer and mix for 10~20 minutes according to mass percentage;

[0033] (2) Add the remaining iron powder and mix again for 30 to 40 minutes.

[0034] Preferably, the rotation speed of the mixer is 15-20 r / min.

[0035] A third aspect of the present invention provides an application of a novel powder metallurgy material for preparing gas spring components.

[0036] Beneficial effects: The new powder metallurgy material provided by the present invention can prepare gas spring parts with good tensile strength and riveting performance, and can be used to replace zinc-aluminum alloy parts to prepare gas spring fixing rings. The tensile strength is not only better than that of zinc-aluminum alloy, but also can meet the ductility required by the gas spring fixing ring. It can reduce the production cost of the gas spring fixing ring without affecting the use of the gas spring fixing ring and improve production efficiency. DETAILED DESCRIPTION

[0037] Example 1

[0038] Example 1 provides a novel powder metallurgy material, which includes the following raw materials, by mass percentage: 0.3% non-metallic powder, 0.5% lubricant, 0.3% processing aid, and metal powder as the balance.

[0039] The metal powder is selected from a combination of iron powder and copper powder.

[0040] The iron powder is water atomized iron powder purchased from Jiande Yitong Metal Powder Co., Ltd., model: 300W.

[0041] The particle size distribution of the water-atomized iron powder is as follows: particles with a particle size greater than 180 μm are ≤1wt%, particles with a particle size less than 180 μm and greater than 150 μm are ≤10wt%; particles with a particle size less than 45 μm are 15-30wt%, and the remainder of particles with a particle size less than 150 μm and greater than 45 μm.

[0042] The water-atomized iron powder has a Mn content of ≤0.15%, a P content of ≤0.015%, and a S content of ≤0.015%.

[0043] The mass percentage of the copper powder is 1%.

[0044] The copper powder is electrolytic copper powder purchased from Tongling Guochuan Electronic Materials Technology Co., Ltd., model: FTD4.

[0045] The copper mass content of the electrolytic copper powder is ≥99.8%.

[0046] The particle size distribution of the electrolytic copper powder is as follows: the maximum particle size is not greater than 100 μm, the particles with a particle size less than 100 μm and greater than 75 μm are ≤ 3 wt %; the particles with a particle size less than 75 and greater than 45 μm are 37-52 wt %, and the particles with a particle size less than 45 μm are 45-60 wt %.

[0047] The non-metallic powder is carbon powder.

[0048] The particle size of the carbon powder is 9.5±0.5 μm.

[0049] The carbon powder is flake graphite purchased from Qingdao Yueshi Graphite Co., Ltd., model: F-1.

[0050] The carbon content of the flake graphite is ≥98.0%.

[0051] The lubricant is zinc stearate, which was purchased from Nantong Xinbang Chemical Technology Co., Ltd.

[0052] The processing aid is manganese sulfide, which was purchased from Yangzhou Xinte Science and Technology Trading Co., Ltd.

[0053] A method for preparing a novel powder metallurgy material comprises the following steps:

[0054] (1) Add 1 / 4 of iron powder, copper powder, non-metallic powder, lubricant, and processing aid into a mixer according to mass percentage and mix for 15 minutes;

[0055] (2) Add the remaining iron powder and mix again for 35 minutes.

[0056] The rotating speed of the mixer is 17 r / min.

[0057] Example 2

[0058] Example 2 provides a novel powder metallurgy material, which includes the following raw materials, by mass percentage: 0.33% non-metallic powder, 0.5% lubricant, 0.3% processing aid, and metal powder as the remainder.

[0059] The metal powder is selected from a combination of iron powder and copper powder.

[0060] The iron powder is water atomized iron powder purchased from Jiande Yitong Metal Powder Co., Ltd., model: 300W.

[0061] The particle size distribution of the water-atomized iron powder is as follows: particles with a particle size greater than 180 μm are less than 1wt%, particles with a particle size less than 180 μm and greater than 150 μm are less than 10wt%; particles with a particle size less than 45 μm are 15-30wt%, and the remainder of particles with a particle size less than 150 μm and greater than 45 μm.

[0062] The water-atomized iron powder has a Mn content of ≤0.15%, a P content of ≤0.015%, and a S content of ≤0.015%.

[0063] The mass percentage of the copper powder is 1.2%.

[0064] The copper powder is electrolytic copper powder purchased from Tongling Guochuan Electronic Materials Technology Co., Ltd., model: FTD4.

[0065] The copper mass content of the electrolytic copper powder is ≥99.8%.

[0066] The particle size distribution of the electrolytic copper powder is as follows: the maximum particle size is not greater than 100 μm, the particles with a particle size less than 100 μm and greater than 75 μm are ≤ 3 wt %; the particles with a particle size less than 75 and greater than 45 μm are 37-52 wt %, and the particles with a particle size less than 45 μm are 45-60 wt %.

[0067] The non-metallic powder is carbon powder.

[0068] The particle size of the carbon powder is 9.5±0.5 μm.

[0069] The carbon powder is flake graphite purchased from Qingdao Yueshi Graphite Co., Ltd., model: F-1.

[0070] The carbon content of the flake graphite is ≥98.0%.

[0071] The lubricant is zinc stearate, which was purchased from Nantong Xinbang Chemical Technology Co., Ltd.

[0072] The processing aid is manganese sulfide, which was purchased from Yangzhou Xinte Science and Technology Trading Co., Ltd.

[0073] A method for preparing a novel powder metallurgy material comprises the following steps:

[0074] (1) Add 1 / 4 of iron powder, copper powder, non-metallic powder, lubricant, and processing aid into a mixer according to mass percentage and mix for 15 minutes;

[0075] (2) Add the remaining iron powder and mix again for 35 minutes.

[0076] The rotating speed of the mixer is 17 r / min.

[0077] Comparative Example 1

[0078] Comparative Example 1 provides a new type of powder metallurgy material, and its specific implementation method is the same as that of Example 1, except that the water-atomized iron powder is replaced by reduced iron powder purchased from Anhui Magang Powder Metallurgy Co., Ltd., model: MHF100.255.

[0079] Comparative Example 2

[0080] Comparative Example 2 provides a new type of powder metallurgy material, and its specific implementation is the same as that of Example 1, except that the water-atomized iron powder is replaced by reduced iron powder purchased from Laiwu Iron and Steel Group Powder Metallurgy Co., Ltd., model: FHY100.25.

[0081] Comparative Example 3

[0082] Comparative Example 3 provides a new type of powder metallurgy material, and its specific implementation method is the same as that of Example 1, except that the water-atomized iron powder has a Mn mass content of 0.10%, a P mass content of 0.09%, and an S mass content of 0.005%. It is purchased from Laiwu Iron and Steel Group Powder Metallurgy Co., Ltd., model: LAP100.29.

[0083] Comparative Example 4

[0084] Comparative Example 4 provides a new type of powder metallurgy material, and its specific implementation is the same as that of Example 1, except that the mass percentage of the non-metallic powder is 0.6%.

[0085] Comparative Example 5

[0086] Comparative Example 5 provides a new type of powder metallurgy material, and its specific implementation is the same as that of Example 1, except that no non-metallic powder is added.

[0087] Performance test: The powder metallurgy materials prepared in Examples 1 to 2 and Comparative Examples 1 to 5 were pressed into shape by a mold, and then sintered in a mesh belt furnace at 1110° C. to obtain a semi-finished product, and the gas spring fixing ring sample was obtained by mechanical processing. The tensile strength of the sample was tested by a JDL-50kN tensile testing machine; the riveting performance of the sample was tested by a PLST6-460A hydraulic riveting machine. If there was no crack in the appearance after riveting, it was marked as OK, and if there was crack, it was marked as NO; the hardness of the sample was tested according to GB / T 230.1-2018 standard.

[0088] Test results:

[0089] Table 1

[0090]

Claims

1. A powder metallurgy material for preparing gas spring parts, It is characterized in that Calculated by mass percentage, it includes the following raw materials: 0.3% carbon powder, 0.2-0.8% lubricant, 0.1-0.5% processing aid, and metal powder remainder; the metal powder is iron powder and copper powder; The iron powder is atomized iron powder, and the atomized iron powder is water-atomized iron powder; the particle size distribution of the water-atomized iron powder is: particles with a particle size greater than 180 μm are ≤1wt%, particles with a particle size less than 180 μm and greater than 150 μm are ≤10wt%; particles with a particle size less than 45 μm are 15-30wt%, and the remainder of particles with a particle size less than 150 μm and greater than 45 μm; the mass content of Mn in the water-atomized iron powder is ≤0.15%, the mass content of P is ≤0.015%, and the mass content of S is ≤0.015%; The mass percentage of the copper powder is 1%, and the copper powder is electrolytic copper powder. The particle size distribution of the electrolytic copper powder is as follows: the maximum particle size is not greater than 100 μm, and the particles with a particle size less than 100 μm and greater than 75 μm are ≤ 3wt%; the particles with a particle size less than 75 and greater than 45 μm are 37-52wt%, and the particles with a particle size less than 45 μm are 45-60wt%; The carbon powder is flake graphite; The processing aid is manganese sulfide or boron nitride.

2. The powder metallurgy material for preparing gas spring parts according to claim 1, It is characterized in that The particle size of the carbon powder is 5-20 μm.

3. The powder metallurgy material for preparing gas spring parts according to claim 1, It is characterized in that The lubricant is selected from one or more combinations of zinc stearate, calcium stearate, magnesium stearate and aluminum stearate.

4. A method for preparing a powder metallurgy material for preparing a gas spring component according to any one of claims 1 to 3, It is characterized in that The following steps are involved: (1) Add 1 / 3~1 / 4 of iron powder, copper powder, carbon powder, lubricant and processing aid into a mixer and mix for 10~20 minutes according to mass percentage; (2) Add the remaining iron powder and mix again for 30 to 40 minutes.

Citation Information

Patent Citations

  • A kind of powder metallurgy material for mold and preparation method thereof

    CN104561773B

  • Powder metallurgy composition containing silicon dioxide as leavening agent and flow velocity enhancer

    CN112276073A

  • Powder for powder metallurgy, green compact and method for producing sintered component

    JP2017066491A